Internalisasi Pendidikan Karakter di Perguruan Tinggi: Studi Kasus di Jurusan Tarbiyah STAIN Ponorogo - Wathoni, Kharisul (Didaktika Religia, 2014)
This study will examine the internalization of character values at the TarbiyahÂ Department of STAIN Ponorogo. It has been found out that STAIN Ponorogo, inÂ particular the Tarbiyah Department, has made efforts to undertake character educationÂ to the students through three patterns: during the learning process, duringÂ process of academic administrative services, and during extracurricular and intraccurricularÂ activities followed by students at STAIN Ponorogo. The charactersÂ to be internalized are honesty, discipline, religiousity, creativity, self-reliance, responsibility,Â tolerance, communication and responsibility